Filogeografia de anfíbios da diagonal de áreas abertas da América do Sul - São Pedro, Vinícius de Avelar (2014)
The ‘dry diagonal’ is a very diverse and biogeographically important region in South America. However, its diversity is still underestimated and little is known about the processes that originated its biota. To investigate the relevance of geological and climatic events in the diversification processes, we conducted a multilocus range-wide approach for Dermatonotus muelleri, a fossorial frog endemic to the dry diagonal. We found two geographically structured lineages, well defined in both mitochondrial (NAD2) and nuclear (POMC and TMEM) genes. The estimates of lineage divergence, between the Miocene and Pliocene, corroborate the idea that Neogene orogeny events were crucial for the main diversification events in the dry diagonal. The influence of Pleistocene climatic fluctuations appears restricted to population size changes of one of the lineages. A great genetic divergence and distinctive ecological niches between lineages suggest the existence of a cryptic non-described species. Partially contrasting with previous works, our results reinforce the need for additional phylogeographic studies approaching other taxa as the only way to better understand the biogeographic history in the dry diagonal.